Social media for social movement: A social media training for Turun Tangan Organization - Dwi Susanti; Prihatin Dwihantoro; Fadillah Sandy; Lintang Muliawanti (Universitas Muhammadiyah Magelang, 2022)
Social media grow rapidly and encourage people to access the information in a quick way. Turun Tangan is a non-profit organization and used social media as tools to share information and expand its network. As such, a social media training is very needed. The training was conducted in three sections, Digital Literacy Skills seminar, Digital Content Creation training, and Copywriting training. The training was held online and there were 100 Turun Tangan volunteers participated in the program. From the training, they get information about basic digital literacy skills and upgrade their digital skills in creating creative digital content and copywriting.